He kākano ahau – identity, Indigeneity and wellbeing for young Māori (Indigenous) men in Aotearoa/New Zealand. (February 2021) - Hamley, Logan; Grice, Jade Le
This article examines how dominant Eurocentric approaches to mental health are unable to address the diverse needs of young Māori men in Aotearoa/New Zealand. Drawing on current health inequities facing Māori and young Māori men in particular, this commentary explores how colonisation has impacted young Māori men in negative ways. Through shaping current health structures in Aotearoa/New Zealand, dominant Eurocentric approaches foreground individualised conceptualisations of Māori ill-health, and then apply predominantly Western therapies to resolve this. These approaches are ill-equipped to address the intergenerational and structural issues which are at the root of mental health disparities for young Māori men. This article adds to a growing body of Indigenous psychology literature that speaks to the inadequacies within (mental) health systems for addressing the ongoing challenges that Māori experience due to colonisation. It further highlights how the intersections among ethnicity/race, class, age and masculinity for Māori men are shaped by colonial discourses. These inadequacies reflect a broader issue of the constraints placed on Māori self-determination by the colonial systems of power in Aotearoa/New Zealand. The article closes by proposing some alternative approaches to supporting Māori wellbeing that centre the needs and aspirations of Māori.